The representation of EFL context-based cultures in an international EYL textbook - Nurhayati, Lusi; Triastuti, Anita; Widodo, Pratomo (LITERA, 2023)
The present content analysis study intended to investigate the cultural contents of an international EYL textbook used in Indonesian private elementary schools. It examined the representation of cultural themes categorized under the big "C" and small "c" cultures and the representation of EFL context-based/Indonesian cultures in each theme. The findings of the study revealed that (1) the book covered all themes, but their representation is not balanced; (2) some aspects of local cultures were represented in the books, but the number was very limited and less varied. The implication of this study suggests that the international EYL textbook should allocate adequate space for local culture. Hence, this could be seen as an opportunity for EYL teachers and practitioners to use their authority and to empower themselves by providing supplementary materials that best suit their local needs. Keywords: culture, themes, local, representation, international, EYL textbook